The manuscripts of Macrobius' Commentary on the Somnium Scipionis - Barker-Benfield, B (1975)
No comprehensive study of the manuscripts of Macrobius' Commentary on the Somnium Scipionis has appeared in print since the edition of Ludwig von Jan in 1848, although in the 1950s A. la Penna published valuable articles in which he announced the importance of the two 9th-cent. manuscripts, Paris lat. 6370 and Paris lat. 16677. The surviving medieval manuscripts of the Commentary, with or without a separate text of the Somnium Scipionis itself, number around 230 - the figure includes fragments but not excerpts. The total for the Saturnalia is just under 100. The Commentary and the Saturnalia are rarely found written together in one manuscript, and the two manuscript traditions are almost entirely separate. The work summed up in the thesis is based on detailed 'codicological' descriptions and collations of sample passages for about 150 out of the total of c. 230 manuscripts of the Commentary. An attempt has been made to apply the skills of the palaeographer and historian of medieval libraries equally with those of the textual critic in extracting palaeographical and textual evidence from a manuscript treated as a whole. The aim of the work is to discover what the manuscripts themselves can contribute towards the history of Macrobius' text in the Middle Ages, and to distinguish families of manuscripts as a preliminary to the establishing of the text. By the beginning of the 12th cent., it is broadly true to say that a 'vulgate' text of Macrobius' Commentary had been established; the tradition by then was so heavily contaminated that the general impression given by later manuscripts is one of total eclecticism. The later manuscripts do not fall into any major divisions, and only occasionally into identifiable localised groups. Although the 150 manuscripts analysed are from all periods, it has been decided to restrict the thesis to the earlier manuscripts, up to the end of the 11th cent. Here two important families of manuscripts can be discerned, which I have christened 'the Φ group' and 'manuscripts of the abbreviated form'. These account for the majority of surviving manuscripts up to c. 1100, but there is still a residue which are difficult to classify. It would be wrong to say that these remaining manuscripts form a third family, for their only common element lies in the fact that they do not belong to one of the two groups. Although I have the information about these manuscripts at hand, I have largely ignored them in the thesis in order to concentrate on those which belong to recognisable families. The thesis falls into two parts. Pt.I consists of chapters in which the ideas suggested by the combination of textual and palaeographical information are elaborated. Pt. II contains full descriptions of most of the major manuscripts discussed in Pt. I. These descriptions are not intended as reading-matter, but as a corpus of reference material to illustrate the background of facts and detailed research on which the speculations of Pt. I are based; they incude a number of discoveries about indivisual manuscripts, e.g. the re-connecting of several sets of membra disiecta. Because of problems of space, it has been decided to tender full descriptions of a limited number of manuscripts rather than summary descriptions of them all; those included represent only a sample of the total work done. In Pt. I, chapter I concerns the subscription of Aurelius Memmius Symmachus, consul of A.D. 485. The implications of the subscription for the very early history of the text are first discussed, and a small piece of new evidence which may possibly have a bearing on the nationality of Macrobius is brought forward. The nine manuscripts which contain the subscription are then listed and analysed, with a view to finding out whether any of them may be direct descendants of the copy corrected by Aurelius Memmius Symmachus. For six of them it is demonstrated that the subscription must have been an addition, either in these manuscripts themselves or in their immediate ancestors; there remain three which may descend from Symmachus' copy. Finally, it is suggested that the ancient manuscript itself survived the Dark Ages, and passed from Ravenna before 485 to the circle of Lupus of Ferrières between 859 and 862; a parallel is drawn between the histories of the ancient copy of Macrobius' Commentary and the miscellany of Rusticus Helpidius Domnulua which was the exemplar of Vat. lat. 4929, and was used by Lupus and his pupil Heiric of Auxerre. Chapter II concerns the oldest surviving manuscript of the Commentary, Paris lat. 6370 (s.ix⅓, ?Tours), and opens with a discussion of the manuscript as it originally stood before correction. C.H. Beeson identified the hand of Lupus in some 9th-cent. corrections; an attempt is made to confirm the suggestion of É. Pellegrin that another 9th-cent. hand which makes additions in the manuscript can be identified as that of Heiric. Chapters III-V concern the Φ group of manuscripts. In ch. III, the three 9th-cent. manuscripts are analysed with regard to provenance and textual relationships. Two are from Fleury, one from Corbie. The discovery that Reg. lat. 1587, fols.65-80, containing a 9th-cent. copy of De senectute, is from the same manuscript as Paris lat. 16677 (Macrobius' Commentary) introduces the definition of a 9th-cent. corpus, Cato de senectute cum Macrobio, which incorporated the Φ strain of Macrobius' text. The chapter ends by tracing the Insular background of Φ. Ch. IV concerns the later descendants of the 9th-cent. Fleury manuscripts, and it is shown that Macrobius was copied and read with great attention at Fleury under Abbo at the turn of the 10th and 11th centuries. Ch. V deals with the members of the Φ group written in Germany, and shows that the 9th-cent. Corbie manuscript, Paris nouv. acq. lat. 454, had two 11-th cent. German descendants. Ch. VI deals with an abbreviated form of the Macrobius' text, containing the mainly astronomical section from I.14, 21 to II.9, 10, found in many German manuscripts of the 10th and 11th centuries. But the earliest manuscript was written in France (Berne 347, fols 1r - 22r, ? Auxerre, s.ix²); a codicological argument is put forward that Berne 347 shows marks of editorial manipulation and is therefore the archetype of the group. The conclusion is that the earliest manuscripts of Macrobius' Commentary were written in the French centres such as Tours, Fleury, and in them can be detected the signs of an Insular pre-history. Although the tradition is heavily contaminated, the definition of the two major groups should help us to establish the text on a new basis.